Peran Meaningfulness to Work dalam Memoderasi Pengaruh Work Engagement terhadap Job Satisfaction pada Karyawan Spa & Village Resort Tembok Bali (Jurnal Ekonomi dan Manajemen, 2024)
This study aims to analyze the relationship between work engagement and job satisfaction, with meaningfulness to work as a moderating variable among employees at Spa Village Resort Tembok Bali. The research employs a quantitative approach using moderation regression analysis. Data were collected from 127 respondents using a Likert-scale questionnaire that has been tested for validity and reliability. The results indicate that work engagement has a positive and significant effect on job satisfaction. Meaningfulness to work also has a significant direct effect on job satisfaction and strengthens the relationship between work engagement and job satisfaction. The regression model incorporating the moderating variable shows a higher R-Square value than the model without moderation, indicating that meaningfulness to work enhances the contribution of work engagement to job satisfaction. The findings highlight the importance of management in creating a work environment that supports engagement and meaningfulness to improve employee job satisfaction.